Penerapan Model Pembelajaran Kooperatif Tipe Murder terhadap Keaktifan dan Hasil Belajar Desain Grafis - Iptihani, Huril; Lutfi, Samsul (Universitas Hamzanwadi, 2019)
This study aimedÂ to determine: The Effect of the Implementation of the Murder Type Cooperative Learning Model Against Student Activities and Learning Outcomes in Graphic Design Subjects Tenth Grade ofÂ TKJ in SMK Bajang NW Ajan 2019/2020 Academic Year. This type of research was quantitative with experimental methods. The research design used was pre-experimental design in the form of one group pretest posttest design. The population of this research wasÂ Â the entire Tenth Grade of TKJ SMK Bajang NW Ajan. The sample in this study was Tenth Grade ofÂ TKJ, amounting to 30 students. Data colleting used tests and observation. Tests were used to measure student learning outcomes and observation sheets were used to measure student learning activities. Data analysis used was the Paired Sample T Test with SPSS software. The results showÂ that: (1) there is an influence of the murder type cooperative learning model on student activity (with a significance value Ï < 0,05); (2) there is an influence of the murder type cooperative learning model on student learning outcomes (with a significance value Ï < 0,05).